Ascosphaera apis as a target for the antifungal activity of symbiotic Bifidobacteria in honey bees - Iorizzo, Massimo; Ganassi, Sonia; Testa, Bruno; Di Donato, Licia Maria; Albanese, Gianluca; Succi, Mariantonietta; Coppola, Francesca; Cozzolino, Rosaria; Matarazzo, Cristina; Di Criscio, Dalila; Tedino, Cosimo; De Cristofaro, Antonio (Frontiers in Insect Science, 2025)
IntroductionThe genus Bifidobacterium is a key component of the honey bee gut microbiota, playing a fundamental role in maintaining host health and colony well-being. Alongside other core genera such as Bombilactobacillus, Gilliamella, Lactobacillus, and Snodgrassella, Bifidobacterium contributes to essential functions including nutrient digestion, immune modulation, and protection against pathogens. Among threats to honey bee health, Chalkbrood disease, caused by fungus Ascosphaera apis, remains a major concern due to detrimental effects on colony strength and honey yield.Materials and methodsWe characterized enzymatic activity and carbohydrate assimilation of nine Bifidobacterium strains isolated from the honey bee intestinal tract. In parallel, we assessed antifungal potential against A. apis strains, focusing on volatile organic compounds (VOCs).Results and discussionNotably, Bifidobacterium asteroides 3CP-2B exhibited enzymatic capabilities supporting digestive functions and metabolism of sugars potentially harmful to honey bees. This strain showed marked antifungal activity against A. apis, mediated by volatile and non-volatile bioactive metabolites. Among VOCs identified, propanoic acid, ethanol, acetic acid, ethyl propionate, and 1-propanol were the most prominent compounds associated with the antifungal effect.